Equity and Efficiency in the Reform of Price Subsidies : A Guide for Policymakers - Cordoba, Juan (Manuals and Guides, 2000)
This text provides guidance to policymakers on how to design and implement sound price-subsidy reforms. It draws on the experience of price-subsidy reform in 28 countries. The authors discuss economic and political considerations and make several recommendations concerning the speed of reform and social protection mechanisms. They discuss how the social impact of reform can be limited by establishing cost-effective and well-targeted temporary social protection mechanisms, and how governments can reduce the risk of political disruption by distributing the initial burden of reform fairly and by clearly explaining the costs and benefits to the public.